Kiriath-Jearim (Deir el-ʿÂzar): archaeological investigations of a biblical town in the judaean hill country - McKinny, Chris (Israel exploration journal, 2018)
This paper discusses the history of research at Deir el-ʿÂzar (Tel Qiryat Yeʿarim), including a discussion of its traditional identification with Kiriath-Jearim and a preliminary report of both the recent archaeological survey and G. Barkay’s salvage excavation, which was carried out in the winter of 1995–1996. Significantly, this paper provides the first modern report on the nature of the archaeology of Kiriath-Jearim (Deir el-ʿÂzar), which includes occupation from the Neolithic period until modern times.